Using wired hart and wirelesshart together for PLC and SCADA system - Thepmanee, Teerawat; Pongswatd, Sawai; Kummool, Sart; Subpayasomboon, Siramet (My University, 2015)
Wireless Technology has promoted in the process automation because it does not require power and communication wiring for field instruments that enables reduced engineering cost. At the same time, end-users consider the developments of process automation by using wireless devices due to the growing of the new plants and replacing analog or wired HART plants. The paper presents a technique to modify wired HART device to be WirelessHART device and to configure it for communication with other WirelessHART devices. A PLC (Programmable Logic Controller) and SCADA system is used to provide centralized device information, historian, and HMI. Installation and configuration techniques of wired HART, THUM adapter or repeater, WirelessHART, HART gateway are described. In addition, engineering and SCADA software are assigned based on OPC to share WirelessHART data with gateway, PLC and SCADA system. The experimental results by using S7-300 Siemens PLC, WW InTouch, and HART devices in level process control are included to confirm the system workability. Moreover, the technique could be applied to collect data for end-user support to quickly and easily gain the benefits of device diagnostic and to decide the plant operation and planning.
Keywords: PLC; Process automation; SCADA; Wired HART; WirelessHART